2018
DOI: 10.3390/en11112870
|View full text |Cite
|
Sign up to set email alerts
|

A New Input Selection Algorithm Using the Group Method of Data Handling and Bootstrap Method for Support Vector Regression Based Hourly Load Forecasting

Abstract: Electric load forecasting is indispensable for the effective planning and operation of power systems. Various decisions related to power systems depend on the future behavior of loads. In this paper, we propose a new input selection procedure, which combines the group method of data handling (GMDH) and bootstrap method for support vector regression based hourly load forecasting. To construct the GMDH network, a learning dataset is divided into training and test datasets by bootstrapping. After constructing GMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Therefore, the results confirm the validity of their proposed short-term wind energy prediction method. Yu et al [16] introduced a new import selection program that combines the group method of data handling and SVR to predict short-term hourly load. After configuring the group method of data handling networks multiple times under the same experimental conditions, they also set the network numerous times.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, the results confirm the validity of their proposed short-term wind energy prediction method. Yu et al [16] introduced a new import selection program that combines the group method of data handling and SVR to predict short-term hourly load. After configuring the group method of data handling networks multiple times under the same experimental conditions, they also set the network numerous times.…”
Section: Related Workmentioning
confidence: 99%
“…Liu et al enhanced GMDH networks by introducing elastic net regression and enriching with difference degree weighting optimization for forecasting hourly loads in data sets pertaining to three locations in China [38] against ANN, SVM, least absolute shrinkage and selection operator (LASSO), ridge regression (RR), and traditional GMDH networks. For South Korea's hourly load data, Yu et al suggested a forecasting methodology based on SVR, which implements GMDH networks and bootstrap methods for the input selection procedure in comparison with different variations of linear correlation (LC) and mutual information (MI) based filter methods [39]. Izzatillaev and Yusupov analyzed hourly electrical energy consumption forecasting in a grid-connected microgrid within a commercial bank by employing GMDH networks and ANN [40].…”
Section: Related Workmentioning
confidence: 99%
“…Special attention is given to forecasting, analysis, and management within the context of smart electric grids. The primary applications of ML in the energy sector include load forecasting, optimisation of generating capacities, ensuring power supply reliability, and analysing and managing energy flows in distribution networks [6][7][8][9][10][11][12]. Additionally, diagnosing and predicting equipment failures is a significant area, contributing to preventing emergencies and minimising downtime in power systems [13][14].…”
Section: Introductionmentioning
confidence: 99%